Biosurfactant production in sugar beet molasses by some Pseudomonas spp. - Onbasli, Dilsad; Aslim, Belma (My University, 2010)
In this study rhamnolipid biosurfactant production was investigated in eighteen strains of Pseudomonas spp.. Rhamnolipid by these strains was determined by a spectrophotometric method in nutrient broth medium (NB). From the 18 strains screened, two Pseudomonas strains (Pseudomonas luteola B17 and Pseudomonas putida B12) which had produced the highest percentage yield of rhamnolipid were examined for rhamnolipid production at different incubation times (24, 48 and 72 hr) and different sugar beet molasses concentrations [1-5% w/v concentration (1-5 g molasses/100 ml water)]. The rhamnolipid production increased with the increase in the concentration of molasses and maximum production occurred when 5 % (w/v) of molasses were used. At the same time, maximum rhamnolipid production occurred after 72 hr of incubation. When the amount of rhamnolipid produced at different incubation times (24, 48 and 72 hr) and with different concentrations of molasses [1-5 % w/v concentration (1-5 g molasses/100 ml water)] by Pseudomonas spp.; was compared, no significant difference in amount of production was seen. These studies show that the waste product from sugar industry may be suggested for important biotechnological processes such as rhamnolipid production.
Keywords: Surface-Active Agents; Pseudomonas; Molasses; Beta vulgaris; Glycolipids; Carbon; 2. Zero hunger